A thermal study of amorphous and textured carbon and carbon nitride thin films via transient grating spectroscopy. (April 2018) - Cometto, Olivier; Dennett, Cody A.; Tsang, Siu Hon; Short, Michael P.; Teo, Edwin H.T.
Abstract: In this study, we are considering a novel way of growing carbon nitride (CN) films by using High Power Impulse Magnetron Sputtering (HiPIMS). Carbon and CN thin films were grown on silicon substrate with varying nanocrystalline texturing: some samples were amorphous while others were either nanocrystalline graphite (for the carbon sample) or fullerene-like (for the CN sample), with both samples having a graphitic nanostructure vertically ordered throughout the film. Their thermal diffusivity was computed using transient grating spectroscopy in order to compare the impact of the material's nanostructure on its thermal property as well as benchmarking the performance of CN. It was found that the thermal properties of carbon thin films were decreased when doped with nitrogen, which is attributed to the increased atomic disorder introduced by the nitrogen cross-linking, impacting the phonon propagation. The impact of nitrogen doping on thermal properties opens new avenues in engineering materials with tailored and varying thermal properties at the microscale. Graphical abstract: Image 1